Profile of Problem-Solving Ability in Junior High School Students on Global Warming Lesson Material - M. Aldiono; Tarzan Purnomo; Tjipto Prastowo (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2023)
Objective: This study aims to determine the profile of problem-solving ability in junior high school students on global warming. Method: This research is preliminary. The study used a quantitative-descriptive research type and a purposive-sampling method. The instrument included a problem-solving ability test with four questions based on the Polya indicator on global warming lesson materials. The research sample consisted of 33 students from class VII-B, JHS Al-Miftah 4 Karang Anyar Ketapang Timur Sampang District East Java Province, who had previously received global warming lesson materials. The research data was analyzed by calculating the average score of the indicator student's problem-solving ability in the form of a percentage. Result: The results were as follows: the interpretation of problem-solving abilities in students is still dominant in the